Awareness of patients regarding restorative and endodontic treatment during COVID-19: A survey - Suneeth Shetty; Maruthi Gupta; U K Ambikatanya; M Maurya (Wolters Kluwer Medknow Publications, 2024)
Objective: The aim of the study was to assess the awareness of patients visiting the dental Outpatient Department of JSS Dental College Hospital regarding coronavirus symptoms and their willingness to get dental treatment done during this period. Materials and Methods: Five hundred and twenty-five patients in the age group of 25-65 years who reported to the department of conservative dentistry and endodontics during 6 months were assessed for coronavirus symptoms using a questionnaire of descriptive statistics and analysis. Results: Patients were willing to undergo treatment during the pandemic (97%). Conclusion: Irrespective of the coronavirus, patients seem to be keen to get either their restorative or endodontic treatment done, which shows that the patients are not completely aware of the spread of COVID-19 infection and awareness programs have to be conducted to educate people.